2000
DOI: 10.1177/1362361300004004002
|View full text |Cite
|
Sign up to set email alerts
|

Why and why not? Factors Influencing Employment for Individuals with Asperger Syndrome

Abstract: The supported employment literature relating to organizational concerns has focused mostly on mild intellectual disability. The purpose of this study is to investigate the area of supported employment for individuals with Asperger syndrome using Prospects - The National Autistic Society’s Supported Employment Service. The study will focus on a comparison of employment factors that influence organizations currently employing an individual with Asperger syndrome with organizations who are not. Findings suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 3 publications
4
42
0
4
Order By: Relevance
“…López and Keenan (2014) conducted a survey that demonstrated that "lack of appropriate understanding from employers and coworkers" is one of the biggest barriers to successful employment. Nesbitt (2000) investigated 69 employers and found that those who were not hiring people on the spectrum (58 % of the total participants) shared some common features, such as being focused on an employee's ability to work in an established way, emphasis on an employee's ability to adapt, concern for potential negative effects, and less open to new information. Richards (2012) indicated that employers' reticence and resistance toward workplace adjustments related to employees' disability, and the reluctance of involving third parties' support, would eventually lead to the termination of employment for people with Asperger's.…”
Section: External Challenging Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…López and Keenan (2014) conducted a survey that demonstrated that "lack of appropriate understanding from employers and coworkers" is one of the biggest barriers to successful employment. Nesbitt (2000) investigated 69 employers and found that those who were not hiring people on the spectrum (58 % of the total participants) shared some common features, such as being focused on an employee's ability to work in an established way, emphasis on an employee's ability to adapt, concern for potential negative effects, and less open to new information. Richards (2012) indicated that employers' reticence and resistance toward workplace adjustments related to employees' disability, and the reluctance of involving third parties' support, would eventually lead to the termination of employment for people with Asperger's.…”
Section: External Challenging Factorsmentioning
confidence: 99%
“…All the studies emphasized that future research should be conducted to examine the employers' as well as the co-workers' attitudes and perceived concerns about hiring and supporting people with ASD. It was suggested that appropriate autism awareness training would help mediate the cost-benefit-oriented decision (López and Keenan 2014;Nesbitt 2000;Richards 2012). …”
Section: External Challenging Factorsmentioning
confidence: 99%
“…L'accumulation d'échecs lors de l'entraînement au travail, ou sur le plan des habiletés personnelles, ou dans la recherche d'un emploi convenable, entraîne des frustrations, une perte d'estime de soi et, pour certains, l'enfermement dans un ensemble de troubles psychiatriques (Jennes-Coussens et al, 2006 ;Nesbitt, 2000). Le pourcentage de personnes inactives atteint 44 % comparativement à 20 % chez les travailleurs sans limitation.…”
Section: Qu'en Est-il Au Québec ?unclassified
“…Other opportunities may include extracurricular school activities related to career interests, internships, service learning, or occupational mentoring to learn and practice work behaviors and gain awareness of a potential professional niche. Additional support on the job during the first few weeks of employment may help adults with ASD, as a mentor or job coach may provide advice about office politics or assist with the facilitation of flexible schedules or job sharing (Hurlbutt & Chalmers, 2004;Nesbitt, 2000;Portway & Johnson, 2005). Such support more easily takes place through the provision of supported employment, but few highfunctioning academically included students with ASD receive such services (Higgins et al, 2008).…”
Section: Employmentmentioning
confidence: 99%
“…As a method to combat these difficulties, coworkers who act as mentors or coaches may provide great help for these individuals in handling the challenges of the workplace (Hurlbutt & Chamlers, 2004;Simone, 2010). This informal support could reduce the need to disclose the ASD diagnosis on the job for accommodations or adjusted expectations, which, while possibly not as risky as doing so during the application or interview process, involves complicated considerations because of poor understanding or information about ASD in the workplace (Meyerling, 2000;Nesbitt, 2000). Cognitive and sensory characteristics associated with ASD can also make completing work itself difficult.…”
Section: Employmentmentioning
confidence: 99%